MENINGKATKAN MUTU PENDIDIKAN DI PERGURUAN TINGGI MELALUI KEPEMIMPINAN STRATEGIK - Lisdawati Muda (LP2M IAIN Sultan Amai Gorontalo, 2017)
One of the succsess at the university organization is observed by the quality of the alumnus who have high perception, have knowledge are based on belief and piety to Allah SWT, so that they can be easly to find job or can create an occupation their selves as a proof of their succsess. To produce the best alumnus always depend on the role of all component at the university. And the leader is determine in reaching the university purpose, through his skills in processing all of leadership strategic.